High-throughput autoantibody profiling of different stages of Schistosomiasis japonica - Xiaorong Zhou; Xi Wang; Jing Xu; Qi Tang; Robert Bergquist; Leming Shi; Zhiqiang Qin (Taylor & Francis Group, 2023)
Infection by the Schistosoma japonicum can result in acute, chronic and late-stage manifestations. The latter often presents with severe organ failures and premature death. Importantly, infection can also produce autoimmune phenomena reflected by the development of autoantibodies. We wished to explore and profile the presence of autoantibodies in sera of patients with different stages of S. japonicum infection with the added aim of providing a reference assisting diagnosis. Blood samples from 55 patients with chronic and 20 patients with late-stage schistosomiasis japonica together, with a control group of 50 healthy people were randomly investigated against a microarray of 121 different autoantigens. In addition, the frequency of antibodies against Schistosoma egg antigen (SEA) was examined. In the sera from patients with chronic schistosomiasis japonica, 14 different highly expressed autoantibodies were detected, while patients with late-stage schistosomiasis were found to express as many as 43 autoantibody specificities together with a significantly higher frequency of antibodies against SEA compared to the control group. The findings presented suggest that autoantibody-based classification of schistosomiasis japonica represents a promising approach for the elucidation of subtypes of the disease. This approach may reflect differential disease mechanisms, which could ultimately lead to better treatment.